Insight into strategies adopted by the residents who passed exit fellowship examination in first few attempts: Strategies by residents to pass final FCPS examination - Ali Khan, Humera Zafar; Ahmad, Amina; Ashar, Abid; Mahmood, Hamid (Journal of Fatima Jinnah Medical University, 2020)
Background: The residents who pass exit fellowship examination in few attempts adopt certain strategies for early success. The lived experiences of residents passing FCPS final examination in few attempts, barriers to success and strategies to overcome those barriers were studied. Participants and methodology: This phenomenological research study was conducted at Services Hospital, Lahore, Pakistan from June 2015 to May 2017. Purposeful snowball sampling was done. Eleven residents who passed their Final FCPS examination in few attempts, in the last 15 years were included in the study. Semi-structured open-ended interview of the residents was audio-recorded and transcribed. Three themes of helpful factors, barriers encountered and suggestions to overcome those barriers to get through the final FCPS examination and the emerging sub-themes were analyzed and textural and structural description were assigned. Results: Three themes were based on the aim of study and their related emerging sub-themes were found. The helpful factors included self-directed learning, peer assisted learning, interactive educational environment, rehearsal and self-determination. Barriers encountered were related to learning difficulties, competing responsibilities and physical and emotional burnout. Lastly, suggestions to overcome the barriers were use of multiple technology based learning strategies, developing self-confidence and self-efficacy together with prioritization of emotional and physical wellbeing. Conclusions: This study found that self-regulation and internal motivation were important strategies for success in the FCPS exit examination. Barriers can be overcome through technology based learning and increased self-efficacy and prioritizing physical and emotional wellbeing.